The Applications of The Max-Min Soft Burge Matrix in Decision Making on The House Selection Model in The Lubuk Minturun Region: Aplikasi Matriks Lembut Kabur Max-Min dalam Pengambilan Keputusan pada Model Pemilihan Rumah di Daerah Lubuk Minturun - Yurniati, Yurniati (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2022)
The need for housing in the city of Padang is still very high. At this time, housing developments in the city of Padang are increasing from year to year. Many private companies offer various types of housing for the people in Padang City. Basically the construction of housing and settlements aims to meet the community's need for housing as part of basic human needs. Efforts to fulfill housing needs are carried out in the context of increasing and equitable distribution of welfare as well as realizing decent housing in a housing environment that is healthy, safe, harmonious, harmonious and orderly. With the development of housing in the city of Padang, the authors use the Max-Min Soft Escape Matrix method in making decisions on house selection, especially in the Lubuk Minturun area. This is a type of qualitative research using the Max-Min Soft Blur Matrix method. The assessment in this study was carried out by a married couple, Mr. Risman and Mrs. Memi. They went to a house buying agent to buy a house. The houses to be selected were 5 houses in different locations. From the application of the Max-Min Soft Blur Matrix method, it is found that the house chosen by Mr. Risman and Mrs. Memi is the first house and third.